A New Device for Characterisation of the Drainage Kinetics of Fibrous Suspensions Under Gravity - Przybysz, Piotr; Kuncewicz, Czesław; Rieger, František (The Journal of Committee of Chemical and Process of Polish Academy of Sciences, 2014)
Gravity dewatering of fibrous suspension is one of basic technological operations in paper production process. Although there are numerous methods to determine dewatering of such suspensions, none of them can measure undisturbed flow of removed water. In the paper the idea and design of a new apparatus for the determination of drainage rate of fibrous suspensions is presented. The apparatus differs from other known devices by minimisation of filtrate flow resistance in the outlet part of the equipment. In the second part of the paper measurements of the drainage rate have been presented. The flow resistance of the fluid through the bottom wire screen in the device was determined. The calculated flow resistance will be used in the developed model of dynamic drainage of fibrous suspensions, which will be discussed in our following paper (Przybysz et al., 2014).
Keywords: drainage; fibrous suspensions; drainage apparatus